(untitled) (The Research of Medical Science Review, 2025)
Objective: To compare rate of postoperative outcomes in patients receiving immunonutrients undergoing radical cystectomy as compared to matched historical controls. Methods: This non-randomized clinical study included 60 individuals (30 controls and 30 cases) between the ages of 35 and 75 of either gender. Patients who received 10-day perioperative Immunonutrition in the form of an arginine-based preparation (Impact Sachet) TM were prospectively included and compared with a retrospective, matched control group who did not receive Immunonutrition. 30-day complication rates, length of hospital stay, return of activity, and return of bowel function were recorded for both groups and analysed to assess differences in outcomes using multivariable binary logistic regression. Results: The median age of the participants was 63 (±11.5 IQR) years, with the study population being 80% male and 20% female. 20 (33.3%) participants experienced complications. We observed no significant difference in postoperative complication rate nor Clavien complication grade between the two groups (p=0.314 and p=0.302, respectively). The average length of hospital stay was six days in the intervention group and 7.5 days in the control group (p=0.041). Similarly, the time to return to bowel function was five days in the intervention group and six days in the control group (p=0.034). According to the multivariable binary logistic regression analysis, female gender (OR: 0.029), length of hospital Stay (OR: 2.509), and duration of surgery (OR: 0.310) were significant predictors of postoperative complication rate. Conclusion: Perioperative immunonutrition in patients with invasive bladder cancer undergoing radical cystectomy was not significantly associated with decreased postoperative complication rate.